Detection 0f interleukin-10 polymorphism and plasmodium falciparum infecti0n ln ardamata idp camp al-geneina town Sudan - Osman, Abshir Ali (2020)
Malaria is the main cause of Sudanese morbidity and death. It contributes an estimated 7.5 million cases and 35,000 deaths annually, mainly because of Plasmodium falciparum (P. falciparum). Host and pathogen genetic factors are linked to the severity of the disease. In the promoter or coding region of cytokine genes, single nuclear polymorphisms (SNPs) alter their transcriptional activation and produce differential cytokine. Interleukin-10 (IL-10) is an anti-inflammatory cytokine that may play an active role in P. falciparum infection. IL-10 polymorphisms are associated with several diseases, including malaria. IL-10 has a highly polymorphic promoter with variations gene transcription, including 1082 G/A, 819 C/T, and 592 C/A. However, polymorphism at 1082 G/A gene is the most extensively studied because of this polymorphism's ability to increase IL-10 production, which correlated with susceptibility or protection against infection. Therefore, it is important to understand the association of P. falciparum infection and IL-10 gene polymorphism to confirm if this polymorphism plays a role in the incidence of P. falciparum infection to develop a more efficient vaccine against the disease. Polymerase Chain Response (PCR) is one of the most common methods for distinguishing malaria parasites from species levels and gene polymorphism detection in specific species. This study aimed at investigating the association of P. falciparum infection with IL-10 gene promoter 1082 G/A polymorphism in the Sudanese population. Thirty-four (34) blood smears of malarial patients from the Ardamata IDP Camp in Al-Geneina Town, Sudan, were enrolled in this study. The samples were first confirmed with nested PCR (nPCR) for Plasmodium infection before proceeding with P. falciparum identification. Further, PCR was then performed to evaluate IL-10 gene 1082 G/A polymorphism in the samples. nPCR showed that out of 34 samples, 17 were malaria positive, and 17 were negative. Interestingly, all the 17-malaria positive samples were confirmed as P. falciparum. Although nPCR has been claimed to be more sensitive and specific, the number of positive samples detected using this method was less than microscopy and ICT analysis. PCR analysis also confirmed that no gene mutation occurs in the malaria positive samples, indicating there was no significant association between IL-10 -1082G/A polymorphism and P. falciparum infection in these samples.